REACTION PATHWAYS AND REACTION PROGRESS FOR THE SMECTITE-TO-CHLORITE TRANSFORMATION: EVIDENCE FROM HYDROTHERMALLY ALTERED METABASITES - Robinson D.; Schmidt S.Th.; de Zamora A.S. (My University, 2002)
The transformation from smectite to chlorite has been interpreted as involving either a disequilibrium chlorite/smectite mixed-layering sequence, or an equilibrated discontinuous sequence involving smectite-corrensite-chlorite. Here, analysis of the smectite to chlorite transition in different geothermal systems leads us to propose that the transformation proceeds via three contrasting reaction pathways involving (i) a continuous mixed-layer chlorite/smectite series; (ii) a discontinuous smectite-corrensite-chlorite series and (iii) a direct smectite to chlorite transition. Such contrasting pathways are not in accord with an equilibrium mineral reaction series, suggesting that these pathways record kinetically controlled reaction progress. In the geothermal systems reviewed the style of reaction pathway and degree of reaction progress is closely correlated with intensity of recrystallization, and not to differences in thermal gradients or clay grain size. This suggests a kinetic effect linked to variation in fluid/rock ratios and/or a contrast between advective or diffusive fluid transport. The mode of fluid transport provides a means by which the rates of dissolution/nucleation/growth can control the reaction style and the reaction progress of the smectite to chlorite transition. Slow rates of growth are linked to the first reaction pathway involving mixed-layering, while increasing rates of growth, relative to nucleation, promote the generation of more ordered structures and ultimately lead to the direct smectite to chlorite transition, representative of the third pathway.
Keywords: CHLORITE; CHLORITE/SMECTITE; MIXED-LAYER; REACTION PROGRESS; SMECTITE